The Mongolian manuscript of the «Bhadracarya» (The King of Aspiration Prayers, The Aspiration for Noble Excellent Conduct) from a Tuvan archive - Mirzaeva, Saglara V. (The New Research of Tuva, 2018)
The article introduces and examines an anomynous Mongolian translation of a well-known Buddhist prayer text «The King of Aspiration Prayers, The Aspiration for Noble Excellent Conduct» (Bhadracarya), preserved at the research archives of the Tuvan Institute for the Humanities and Socioeconomic Studies.The author provides basic information on the literary history of this text within the tradition of the Mahayana Buddhism, listing the major variations between the manuscript text and canonical translations of the Bhadracarya.Also provided is the transliteration of the text into contemporary Mongolian and a parallel Russian translation.
Keywords: Bhadracarya; «The King of Aspiration Prayers; The Aspiration for Noble Excellent Conduct»; manuscript; Mongolian language; translation; archives; TIHSES (TGGPI); Tuva